Integrating community assets, place-based learning, and career development through project-based learning in rural settings - Kizys, DeNae; Lotter, Christine; Perez, Lucas; Gilreath, Rachel; Limberg, Dodie (Frontiers in Education, 2025)
Our study investigates the first year of a two-year place-based education (PBE) professional development model that focuses on career development in rural middle schools through project-based learning (PBL) units. Rural science, technology, engineering, and mathematics (STEM) educators face unique challenges, including geographic isolation, limited resources, and reduced access to professional development opportunities, which can hinder the effective integration of career-oriented learning in the classroom. We addressed these challenges by implementing professional development in which school counselors and teachers collaborate to design PBL units aligned with rural community local needs and STEM careers. Using a descriptive multiple-case study methodology to document the experiences of three teams of educators, we used cross-case analysis to explore how the teams integrated PBL and PBE principles to foster meaningful learning experiences and enhance career awareness among students. The research questions focused on each team’s implementation of the PBL units based on key PBL design elements and how they integrated local community connections and places. Initial findings suggest that while teams effectively engaged with community members and integrated STEM career connections, they faced challenges in broadly applying learning and assessment practices. We highlight the potential of PBE to enhance rural STEM education and emphasize the need for long-term professional development to equip teachers with the skills necessary to integrate STEM content and career development effectively.